The Bechdel Test in Russian fanfiction: The Portrayal of Women - Leila O. Algavi; Irina I. Volkova; Alina V. Kharchenko; Mariam Jorjikia (RUDN Journal of Studies in Literature and Journalism)
There are very few discussions about the necessity of a syllabus on the study of fanfiction in the professional training programs of Russian teachers and university professors. The educational potential of fan art is still underestimated, although the possibility of using fan works, especially fan fiction, in pedagogical activities was first put on the media education agenda more than ten years ago. Fic writers are creatively and communicatively active schoolchildren and students the very social group the efforts of teachers are targeted to. Fan writings can be considered as additional empirical material for the study of motivation and development of students’ special skills. This article presents the results of an analysis of Russian language fanfics based on the film series: Alien (1979), Aliens (1986), Alien 3 (1992), Alien Resurrection (1997), Prometheus (2012), and Alien: Covenant (2017). The hypothesis of the involvement of Russian-speaking fic writers in feminist notions of gender, as well as gender impartiality, was tested. The Bechdel Test, adapted by the authors, was used as a means of analysis. It is the first time the means were applied to such fanfiction research. The results partially disproved the hypothesis. The case was tested in the 2022–2023 academic year as part of a special course program for students of the evening Department of the Faculty of Philology at the RUDN University and was approved by the teachers as a valuable source of information about the worldview of modern youth.